The Influence of Teaching Empowerment and Motivation towards Lecturers’ Performance at the Department of Management of IBI Darmajaya Bandar Lampung - Betty Magdalena (Politeknik Negeri Lampung, 2012)
The purpose of this study was to determine the effect of partial and simultaneous empowerment and motivation to the performance of lecturers at the Department of Management IBI Darmajaya Bandar Lampung. Type of measurements used was the explanatory research, that is the study of several variables which relates variables, and then analyzes them, and searches for solutions and their implications on the object of research. The results showed that empowerment (X1) affected significantly lecturers’ performance showed by the results of statistical tests where the value t-count > t-table (4.072 > 1,701). Motivation (X1) has significant influence towards lecturers’ performance (Y) where the statistical test results showed the value of t-count > t-table (3.535 > 1.701). Similarly, empowerment and motivation significantly influenced lecturers’ perforamance at once. It was based on the result of statistical test indicating that F-value was 8.774 with a significance level of 0.000 (Prob. Sig = 0.000). obtained value of F table with df (degree of freedom) = nk = 30 – 2 = 28 of 3.30 indicates that the magnitude of the calculated F (8.774) which was calculated F value > F table (8.774 > 3.39). Simultaneous empowerment and motivation with lecturers’ performance were showed by the result of the coefficient of determination (R2) of 0,687. It means that 68,7% (percent) of the variation of the changes in the influence of empowerment and motivation can explain the change of lecturers’ performance. Whereas 31,3% (percent) remaining is the effect of variables or other factors outside the model. Keywords : empowerment, motivation, and lecturers’ performance.